Ultrasound technology has limited ability to predict carcass yield grade of lightweight, short-fed stocker cattle - Lawrence, S.J.; Kreider, S.E.; Higgins, James J.; Allen, L.; Epp, M.P.; Ritter, P.; Blasi, Dale A.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
The majority of cattle fed in commercial feedlots are processed and placed into pens without sorting into groups of uniform size and body condition. As a result of the variability in weight and condition, this management practice may lead to some cattle being fed beyond their optimal harvest point, whereas others are underconditioned and harvested prematurely, and thus fail to reach desired weight or quality grade necessary to attract available carcass premiums. Our objective was to determine if ultrasound technology could be utilized with lightweight calves as a means of predicting carcass fat thickness and yield grade outcomes. If successful, ultrasound could be a useful means of sorting cattle into uniforms groups to improve marketing.
Keywords: Cattle; Ultrasound; Yield grade; Carcass